2021
DOI: 10.29219/fnr.v65.7610
|View full text |Cite
|
Sign up to set email alerts
|

Kiwifruit defense protein, kiwellin (Act d 5) percutaneously sensitizes mouse models through the epidermal application of crude kiwifruit extract

Abstract: Background: Kiwifruit is a popular fruit consumed worldwide and is also used as a cosmetic ingredient. However, it is known to cause allergic reactions in humans. Recent studies have suggested an association between food allergy and food allergens entering the body via the skin. However, percutaneously sensitizing kiwifruit allergens have not been identified in human studies or in animal models. Objective: This study aimed to identify kiwifruit proteins that percutaneously sensitized mice through the epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…It is good to establish an animal model for allergic diseases; however, it remains challenging to apply it to the natural human sensitisation, as the sensitisation through unnatural pathways may result in varying symptoms, for instance, the nasal and intradermal sensitisation for house dust mite in mouse models showed different results (Dijoux et al., 2023 ). However, it has been reported that some allergy symptoms can be induced through artificial ways, such as injecting peanut powder to create a mouse model for peanut allergy (Dolence, 2021 ), or using kiwifruit extract through skin contact to establish a model (Kinugasa et al., 2021 ). The mouse model constructed in this study may add additional knowledge in the areas of urticaria, pruritus and erythema induced by insect bites.…”
Section: Discussionmentioning
confidence: 99%
“…It is good to establish an animal model for allergic diseases; however, it remains challenging to apply it to the natural human sensitisation, as the sensitisation through unnatural pathways may result in varying symptoms, for instance, the nasal and intradermal sensitisation for house dust mite in mouse models showed different results (Dijoux et al., 2023 ). However, it has been reported that some allergy symptoms can be induced through artificial ways, such as injecting peanut powder to create a mouse model for peanut allergy (Dolence, 2021 ), or using kiwifruit extract through skin contact to establish a model (Kinugasa et al., 2021 ). The mouse model constructed in this study may add additional knowledge in the areas of urticaria, pruritus and erythema induced by insect bites.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that allergic reactions by percutaneous sensitization are caused by various foods. In our previous studies, we identified the major percutaneously sensitizing allergen candidates in soybean [ 3 , 4 ], cherry [ 5 ], and kiwi [ 6 ]. Ovalbumin (OVA) and lactoglobulin were also reported to be percutaneously sensitizing allergens in egg and milk, respectively [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%